Hypothalamic Fatty Acids and Ketone Bodies Sensing and Role of FAT/CD36 in the Regulation of Food Intake - Le Foll, Christelle (Frontiers in Physiology, 2019)
The obesity and type-2 diabetes epidemic is escalating and represents one of the costliest biomedical challenges confronting modern society. Moreover, the increasing consumption of high fat food is often correlated with an increase in body mass index. In people predisposed to be obese or already obese, the impaired ability of the brain to monitor and respond to alterations in fatty acid (FA) metabolism is increasingly recognized as playing a role in the pathophysiological development of these disorders. The brain senses and regulates metabolism using highly specialized nutrient-sensing neurons located mainly in the hypothalamus. The same neurons are able to detect variation in the extracellular levels of glucose, FA and ketone bodies as a way to monitor nutrient availability and to alter its own activity. In addition, glial cells such as astrocytes create major connections to neurons and form a tight relationship to closely regulate nutrient uptake and metabolism. This review will examine the different pathways by which neurons are able to detect free fatty acids (FFA) to alter its activity and how high fat diet (HFD)-astrocytes induced ketone bodies production interplays with neuronal FA sensing. The role of HFD-induced inflammation and how FA modulate the reward system will also be investigated here.